2018
DOI: 10.1101/473967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fetal and trophoblast PI3Kp110α have distinct roles in regulating resource supply to the growing fetus

Abstract: 32Previous studies suggest that the placental supply of nutrients to the fetus adapts according to fetal 33 demand. However, the signaling events underlying placental adaptations remain largely unknown. Earlier 34 work in mice has revealed that loss of the phosphoinositide 3-kinase p110α impairs feto-placental growth 35 but placental nutrient supply is adaptively increased. Here we explore the role of p110α in the epiblast-36 derived (fetal) and trophoblast lineages of the conceptus in relation to feto-p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…While fetuses are growth-restricted in early gestation in this PI3K-p110α deficient mouse model, the deficit in fetal growth is less towards term as the morphologically impaired placenta adaptively transports more glucose and amino acid (system A) to the fetus . Cell-specific gene targeting in mice has since revealed that retention of PI3K-p110α signalling ability in the trophoblast lineage of the developing conceptus is critical for mediating the adaptive upregulation of placental system A amino acid transport that is optimizing fetal growth towards term (Lopez-Tello, Khaira, et al, 2019). Other work has indeed highlighted the important role for PI3K signalling in promoting the formation and function of trophoblast lineages (Lee et al, 2019).…”
Section: Pi3kmentioning
confidence: 99%
“…While fetuses are growth-restricted in early gestation in this PI3K-p110α deficient mouse model, the deficit in fetal growth is less towards term as the morphologically impaired placenta adaptively transports more glucose and amino acid (system A) to the fetus . Cell-specific gene targeting in mice has since revealed that retention of PI3K-p110α signalling ability in the trophoblast lineage of the developing conceptus is critical for mediating the adaptive upregulation of placental system A amino acid transport that is optimizing fetal growth towards term (Lopez-Tello, Khaira, et al, 2019). Other work has indeed highlighted the important role for PI3K signalling in promoting the formation and function of trophoblast lineages (Lee et al, 2019).…”
Section: Pi3kmentioning
confidence: 99%